Highly Efficient White Organic Light-Emitting Diodes with Controllable Excitons Behavior by a Mixed Interlayer between Fluorescence Blue and Phosphorescence Yellow-Emitting Layers - Chun-Hong Gao; Xiao-Bo Shi; Dong-Ying Zhou; Lei Zhang; Zhao-Kui Wang; Liang-Sheng Liao (International Journal of Photoenergy)
A highly efficient hybrid white organic light-emitting diode (HWOLED) has been demonstrated with a mixed interlayer between fluorescent blue and phosphorescent yellow-emitting layers. The device structure is simplified by using a controllable fluorescence-mixed interlayer-phosphorescence emission layer structure. The electroluminance (EL) performance can be modulated easily by adjusting the ratio of the hole-predominated material to the electron-predominated material in the interlayer. It is found that the HWOLED with a ratio of 3 : 2 exhibits a current efficiency of 34 cd/A and a power efficiency of 29 lm/W at 1000 cd/m2 with warm white Commission Internationale de l’Eclairage (CIE1931) coordinates of (0.4273, 0.4439). The improved efficiency and adaptive CIE coordinates are attributed to the controllable mixed interlayer with enhanced charge carrier transport, optimized excitons distribution, and improved harvestings of singlet and triplet excitons.